Access to HIV testing and factors associated among sexual minority women in a metropolitan region of the Brazilian Amazon - Janaína de Freitas Vale; Wanderson Santiago de Azevedo Júnior; Paula Regina Barbosa de Almeida; Adinaldo Moreira Martins; Flavine Evangelista Gonçalves; Eliã Pinheiro Botelho; Fabianne de Jesus Dias de Sousa; Cintia Yolette Urbano Pauxis Aben-Athar; Luiz Fernando Almeida Machado; Glenda Roberta Oliveira Naiff Ferreira (Scientific Reports)
Abstract In Brazil, health policies implemented over the last three decades have enabled rapid testing for HIV to be made available in primary health care services. However, although these policies are national, the implementation of actions is not uniform, as they depend on the local management of local health systems. In this context, the study identified the proportion of women from sexual minorities who had never tested for HIV and the factors associated with access, in a Metropolitan Region of the Brazilian Amazon. This was an observational, cross-sectional study, conducted from data collected from July 21, 2022 to April 11, 2024, in the Brazilian Amazon. The study included women, aged 18 or over living in the study area who self-declare and self-identify as lesbian, bisexual, pansexual or asexual. The dependent variable: participants were asked if they had ever been tested for HIV in their lifetime. The independent variables were the access components: predisposing, facilitating and necessary. 301 women from sexual minorities participated in the study, 42.2% of whom had never tested for HIV. In the final model, multiple backward logistic regression was performed, the highest chances of never having been tested for HIV were participants aged 18 to 30 years (OR 2.99; p = 0.038); with income less than or equal to 1 minimum wage (OR 1.91; p = 0.026); participants who did not have children (OR 6.67; p = 0.012); and those who did not have an active sexual life (OR 4.73; p = 0.006). While the lowest chances of never having tested for HIV were among participants who used drugs OR 0.44; p = 0.008) and women who had already had an STI (OR 0.20; p = 0.044). Although the testing prevalence was below 50%, the study identified that the combined prevention strategy has reached the most vulnerable populations.